2022
DOI: 10.1021/acsami.2c13805
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bacteria In Vitro and In Vivo by Self-Assembled DNA-Silver Nanocluster Structures

Abstract: Antimicrobial nanomaterials hold great promise for bacteria-infected wound healing. However, it remains a challenge to balance antimicrobial efficacy and biocompatibility for these artificial antimicrobials. Here we employed biocompatible genetic molecule DNA as a building material to fabricate antimicrobial materials, including self-assembled Y-shaped DNA-silver nanocluster composite (Y-Ag) and Y-Ag hydrogel (Y-Ag-gel). We demonstrate that macroscopic and microcosmic DNA-Ag composites can effectively inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The AgNPs exhibited effective antibacterial activity The advantages of DNA are its biocompatibility and its molecular recognition ability [82]; moreover, DNA, thanks to its affinity for metal cations, is a suitable candidate for metal nanoparticles preparation [83,84]. For example, Liu et al synthesized and investigated the antibacterial activity of Y-shaped DNA-Ag nanoclusters (DNA-AgNCs), and also developed a hydrogel for wound healing [85]. The Y-shaped DNA-AgNCs (named Y-Ag) were synthesized, starting from three oligonucleotide strands (to form the Y structure) in the presence of NaBH 4 and AgNO 3 .…”
Section: Silver Nanoparticles Functionalized By Biomoleculesmentioning
confidence: 99%
“…The AgNPs exhibited effective antibacterial activity The advantages of DNA are its biocompatibility and its molecular recognition ability [82]; moreover, DNA, thanks to its affinity for metal cations, is a suitable candidate for metal nanoparticles preparation [83,84]. For example, Liu et al synthesized and investigated the antibacterial activity of Y-shaped DNA-Ag nanoclusters (DNA-AgNCs), and also developed a hydrogel for wound healing [85]. The Y-shaped DNA-AgNCs (named Y-Ag) were synthesized, starting from three oligonucleotide strands (to form the Y structure) in the presence of NaBH 4 and AgNO 3 .…”
Section: Silver Nanoparticles Functionalized By Biomoleculesmentioning
confidence: 99%
“…[23] AgNCs also can be synthesized and stabilized in aqueous solution using DNA as scaffolds (referred to as DNAtemplate AgNCs). [32][33][34] Therefore, constructing DNA hydrogels using DNA-templated AgNCs can offer an ideal antibacterial scaffold for M2EVs in the treatment of diabetic alveolar bone defects (DABD). On the one hand, the synergistic cooperation of M2EVs and AgNCs can accelerate the healing of DABD in pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…These liposomes have been found to accumulate at low levels in a variety of organs including the lungs, kidneys, and liver and have shown no indication of toxicity . Previous studies have also shown that DNA-AgNCs are nontoxic to mammalian cells. To further investigate the biosafety of DNA-Ag 16 NC-loaded liposomes, the behavior and body weights of mice were monitored after the delivery of a mixture of DNA-Ag 16 NC-loaded liposomes and FITC-Dextran. These mice were monitored to determine any changes in movement, grooming, nest building, and interactions with cage mates.…”
Section: Resultsmentioning
confidence: 99%